Combination of caspofungin and low‐dose trimethoprim/sulfamethoxazole for the treatment of severe Pneumocystis jirovecii pneumonia in renal transplant recipients. Issue 11 (23rd October 2013) - Tu, Guo‐wei; Ju, Min‐jie; Xu, Ming; Rong, Rui‐ming; He, Yi‐zhou; Xue, Zhang‐gang; Zhu, Tong‐yu; Luo, Zhe
Abstract: Pneumocystis jirovecii pneumonia (PJP) is a severe and life‐threatening complication in immunocompromised patients. Trimethoprim/sulfamethoxazole (TMP‐SMZ) is well known for its effectiveness as prophylaxis of PJP. However, the use of TMP‐SMZ is associated with various adverse effects that may not be tolerated by critically ill patients. Caspofungin is recommended for invasive fungal infections, but the treatment of PJP after solid organ transplantation (SOT) is an off‐label use of this drug. In this study, three cases of severe PJP in renal transplant recipients treated with a combination of caspofungin and low‐dose TMP‐SMZ were presented. Initial findings indicated that the combined treatment may be beneficial for the treatment of PJP and decrease the incidence of TMP‐SMZ‐related adverse effects.